The Effect of Financial Ratios Towards Earning Per Share of Infrastructure Companies of the Indonesian Stock Exchange Infrastructure Sub Sector Indices - Hutabarat, Francis M.; Simbolon, Maropen R. (Jurnal Ekonomis, 2013)
Indonesia is a develop country that had its ups-and-downs. The economic crisis on 2008 has suffered many countries. Suddenly the world stops to a glance of a promising new hope, which is Indonesia. A new-turn appears in the economy of Indonesia. Indonesia immediately showed great potential after becoming known in the international community. Indonesian Industries in the infrastructure sector is currently shows an up-trend and will probably continue to rise given the magnitude of the housing market and the need to build. Thus, the growing and development of infrastructure sector gives question to investor whether they can see the financial performance of the said company and how does it affect the Earning-per-share of the company. The purpose of the study is to find out whether the financial ratios are affecting Earning per share of Infrastructure companies listed in the Indonesian Stock Exchange. Based on the sample taken from annual report data from the 2008-2012 and analysis is used to estimate the relationship between the financial ratio and Earning-per-share. The results shows that there is a significant correlation of financial ratios namely return on equity (r = 0.887) on Earning per share of PT. Adhi Karya. The results are significant at Î± = 0.05. Therefore, this indicates that financial ratios of the company namely return on equity are able to predict the changes of Earning-per-share of PT. Adhi Karya. However, the rest of the companies shows that their financial ratios have no significant correlation towards the Earning-per-share of the companies. Keywords: Earning-per-share, Return on Asset, Return on Equity, Current Ratio, Debt to Asset, Debt to Equity